Outcomes of transoral laser microsurgical management of T1b stage glottic cancer. Issue 5 (14th February 2017) - Song, J A; Rigby, M H; Trites, J; Hart, R D; Taylor, S M
Abstract: Objective: This study aimed to evaluate the oncological and voice outcomes of transoral laser microsurgery for tumour stage T1b stage glottic cancer patients. Methods: A prospective cohort study in a tertiary care head and neck cancer centre included tumour–node–metastasis stage T1b N0 M0 glottic cancer patients scheduled to undergo transoral laser microsurgery from January 2002 until June 2014. Kaplan–Meier five-year analyses of local control, overall survival, disease-specific survival and laryngeal preservation were performed. Voice Handicap Index-10 scores and maximum phonation times were also recorded. Results: Twenty-one participants with a mean age of 66.8 years were enrolled. The mean follow up was 56.5 months. Kaplan–Meier 5-year survival analysis illustrated a local control rate of 82 per cent, overall survival of 88 per cent, disease-specific survival of 100 per cent, and laryngeal preservation of 100 per cent. The pre-operative Voice Handicap Index-10 score was 19.1 ± 9.47 (mean ± standard deviation (SD)) and the post-operative scores were 13.5 ± 9.29 at three months, 10.44 ± 9.70 at one year and 5.83 ± 4.91 at two years. The pre-operative maximum phonation time was 16.23 ± 5.46 seconds (mean ± SD) and the post-operative values were 14.44 ± 6.73 seconds at three months, 15.27 ± 5.71 seconds at one year and 14.33 ± 6.44 seconds at two years. Conclusion: Transoral laser microsurgery yields relatively high rates of oncological control and acceptable voice outcomes, and thus shows utility as a primary treatment modality for T1b glottic cancer.